OCCUPATIONAL SAFETY STANDARDS IN THE CONSTRUCTION INDUSTRY: A KAP STUDY FROM DISTRICT LAHORE, PUNJAB PAKISTAN - Siddiqui, Ayesha; Arshad, Muhammad; Afzal, Dr Afzaal (PAKISTAN ISLAMICUS (An International Journal of Islamic & Social Sciences), 2023)
Occupational safety standards are characterized as a complex set of regulations, procedures, methods, and guidelines that protect workers and ensure their safety at the workplace. These standards are designed to reduce the risk of incidents, injuries, and death in the risky nature of workplaces like the construction industry. Occupational safety standards in the construction industry are significantly associated with the protection of social, physical, psychological, and environmental hazards such as harmful materials, slips and falls, dangerous machinery, long working hours, life & health threats, welfare & basic rights, emergency response & safety tools and compensation among others. This study explores the knowledge, attitude, and practice (KAP) of occupational safety standards in the construction industry in Lahore, with the objective of identifying the factors influencing the KAP of safety standards, the degree to which safety standards are being implemented, and the challenges that workers face in adhering to safety standards. The study employed a mixed-methods approach and primary data was collected through focus group discussions and surveys of 384 respondents. The findings indicated that there is a need for significant improvement in the safety policies and practices in the construction industry. The workers have a low level of KAP and a huge proportion of workers were not following safety protocols.